Slaves or Mercenaries: Milton Friedman and the Institution of the All-Volunteer Military - John D. Singleton (Duke University, Center for the History of Political Economy (CHOPE), 2014)
Milton Friedman was the leading public proponent for an all-volunteer military. This chapter traces his influence upon the national debate over conscription, which culminated in Friedman's service on the Gates Commission. Friedman's argument relied on economic reasoning and appeal to cost-benefit analysis. Central was his conjecture that the social cost of the draft, which imposed an "implicit tax" on draftees, exceeded that of the all-volunteer military. This was supported by the work of Walter Oi. Friedman's position attracted support both within the conservative movement and from across the political landscape, allowing Friedman to form coalitions with prominent individuals otherwise in disagreement with his politics. With the social context ripened by the draft and the Vietnam War, Friedman's argument echoed in influential circles, reaching policymakers in Washington and Martin Anderson on the Nixon advising team. The successful institution of the all-volunteer armed force reflected Friedman's intellectual entrepreneurship.
Keywords: B20; B31; 330; Military draft; conscription; all-volunteer armed force; Gates Commission; Vietnam War; implicit tax; Walter Oi; Martin Anderson